HOUSEHOLD WASTE MANAGEMENT IN MEDAN CITY - Mutia Arda; Delyana Rahmawany Pulungan; Dewi Andriany; Yayuk Hayulina (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
The main problem in the solid waste sector in Medan City is the large number of illegal dumping. This study is to obtain an overview of the waste management that has been carried out so far, to inventory the problems of waste management system, to design a waste management model, and to provide recommendations for waste management system. This research used descriptive qualitative method. Based on the SSK instrument, it was known that the diagram of the waste sanitation system in Medan City had 6 categories. There were 18 villages in Medan City at very high risk category, 7 villages in the high-risk category, 51 villages at moderate risk category, and 75 villages at low risk category. Waste zoning in Medan City consists of 4 zones. Based on SWOT analysis which determine the objectives, targets and strategies for developing solid waste management in Medan City was in the fourth quadrant, it was a defensive strategy. The position of internal and external factors in the solid waste sub-sector in this quadrant showed that weaknesses and threats were more dominant than strengths and opportunities.